The Impact of ABCB1 SNPs on Tacrolimus Pharmacokinetics in Liver or Kidney Transplant Recipients: A Meta-analysis - Li, Ze; Wang, Xiaozhen; Li, Dandan; Cheng, Sheng; Dong, Yiwen; Yang, Hongge; Li, Xingang (Current Pharmaceutical Design, 2023)
Purpose: We aimed to investigate the association between ATP Binding Cassette Subfamily B Member 1 (ABCB1) single nucleotide polymorphisms (SNPs) and the pharmacokinetics of tacrolimus. Methods: A search was conducted in Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science (SCI), MEDLINE, and Embase from inception to November 2022. Outcomes included weightadjusted daily dose (DD) and dose-adjusted trough concentration (C0/Dose). Results: A total of 1059 liver or kidney transplant recipients from 14 publications were included. For adult liver transplantation recipients, DD of ABCB1 3435C>T CC carriers was 0.03 mg/kg/day (WMD = 0.03, 95% CI: 0.01 to 0.05, I2 = 0%) higher than ABCB1 3435C>T T carriers at post-transplantation 137;¤ 7 days; C0/dose of ABCB1 3435C>T CC carriers were 31.88 (WMD = -31.88, 95% CI: -62.32 to -1.45, I2 = 83.5%) or 34.61 (ng/ml)/(mg/kg/day) (WMD = -34.61, 95% CI: -65.26 to -3.97, I2 = 55.3%) lower than ABCB1 3435C>T T carriers at post-transplantation 137;¤ 7 or 14 days, respectively. No difference in C0/dose was observed for ABCB1 2677G>T/A or ABCB1 1236C>T SNPs in both liver and kidney transplant recipients. Conclusion: ABCB1 3435C>T SNP might have a potential impact on tacrolimus pharmacokinetics in the early stage after liver transplantation, indicating the probability of individualized immunosuppressive therapy based on genetic polymorphism. Given some limitations, further well-designed prospective studies are warranted to validate these conclusions..
Keywords: transplant recipients